1070 Cerebral Blood Flow Changes in Preterm Neonates Requiring Resuscitation at Birth. (October 2012) - Ahmed, N; Sundaram, V; Kumar, P
Abstract : Background: Hypoxia in the perinatal period causes increase in cerebral blood flow followed by a decrease. CBF data is not available for preterms. Objectives: To study CBF changes in Anterior and Middle cerebral arteries (ACA & MCA) of asphyxiated preterm neonates (< 34 weeks). Setting: Level III Neonatal unit in Northern India, PGIMER, Chandigarh. Subject and Interventions: This is a subgroup analysis of a RCT comparing 21% vs 100 % oxygen for resuscitation. CBF was measured in ACA and MCA at 6±2, 12±2 and 24±4 hours. Peak systolic velocity (PSV) cm/s, End diastolic velocity (EDV) cm/s, Resistance index (RI), Pulsatality index (PI), Systolic diastolic ratio (S/D) and Velocity time integral (VTI) were measured using Philips ultrasonography machine. Results: CBF was measured in 57 neonates. Mean gestation and weight was 31±1.3 weeks and 1400±358 g. HIE was seen in 24 babies (42%). PSV and VTI showed an increasing trend whereas S/D showed a decreasing trend as age increased. PSV [29.2 (23.7–34.2), 28.3 (23.9–33.4) and 33.9 (29.6–37.8) cm/s, p=0.02), VTI (6, 6.5 and 8 cm, p=0.002) and S/D (4.1 (3.07–6.6), 4.03 (3.3–5.4) and 3.8 (3.1–4.7), p=0.01) in the MCA showed significant trend at 6, 12 and 24 hrs respectively. No such trend could be observed in the ACA. On comparing 21% and 100% oxygen groups no difference were observed. Conclusion: CBF indices (PSV, VTI & S/D) of MCA showed a significant increase from 6 to 24 hrs. No difference was observed on comparing 21% with 100% oxygen.